Idylla/testament - wiersze przebrane - Piotrowiak, Miłosz (Wydawnictwo Uniwersytetu Śla̜skiego, 2013)
Zsfassung in engl. u. franz. Sprache
Keywords: Aufsatzsammlung; Polish poetry; Sentimentalism in literature; Wills in literature